Case 3485: Lychnorhiza lucerna Haeckel, 1880 (Cnidaria, Scyphozoa, Rhizostomeae): proposed conservation of generic and specific names. - Morandini, André Carrara (Bulletin of Zoological Nomenclature, 2009)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the generic name Lychnorhiza Haeckel, 1880 for a genus of scyphozoan jellyfish (Cnidaria, Scyphozoa) from Central and South America and the Malayan Archipelago. The name is threatened by a senior synonym, Rhacopilus Agassiz, 1862, unused since its original description. It is also proposed to conserve the specific name Lychnorhiza lucerna Haeckel, 1880 (type species of the genus Lychnorhiza). The nomenclatural stability of this name is threatened by a senior subjective synonym, Rhizostoma cruciata Lesson, 1830.
Keywords: Central and South America; Cnidaria; Lychnorhiza; Lychnorhiza lucerna; LYCHNORHIZIDAE; Malayan Archipelago; Nomenclature; Rhizostoma; Rhizostoma cruciata; Rhizostomeae; Scyphozoa; scyphozoan jellyfish; taxonomy